Dampak Perselingkuhan dalam Perspektif Hak Asasi Manusia - Alfianus Dianomo; Giovani Diamanti; Weldi Lelung; Edward Mere; Gerren F. X. Maweikere (Jurnal Seri Mitra (Refleksi Ilmiah Pastoral), 2026)
Infidelity occurs in couples who have established norms of emotional and physical intimacy, which are then disrupted by a relationship with another person. This relationship can be either emotional or sexual. This paper examines a case of infidelity involving a married couple with children. The purpose of this paper is to examine the context of infidelity cases, assessed based on human rights values. The research method used in this paper is a qualitative case study, in which the author provides a comprehensive and in-depth description of cases and phenomena occurring in society, in this case, infidelity. The author then interprets this phenomenon from a human rights perspective or humanitarian values. From the results of this paper, the author concludes that infidelity violates human rights values, including human dignity, the right to physical and mental health, and the right to family protection.